Ответ:
Пошаговое объяснение:
![\left\{{{\frac{2x^2-10x+6}{x-5}\leq x}\atop{1+log_6(4-x)\leq log_6(16-x^2)}}\right. \left\{{{\frac{2x^2-10x+6}{x-5}\leq x}\atop{1+log_6(4-x)\leq log_6(16-x^2)}}\right.](https://tex.z-dn.net/?f=%5Cleft%5C%7B%7B%7B%5Cfrac%7B2x%5E2-10x%2B6%7D%7Bx-5%7D%5Cleq%20x%7D%5Catop%7B1%2Blog_6%284-x%29%5Cleq%20log_6%2816-x%5E2%29%7D%7D%5Cright.)
ОДЗ
0\\16-x^2>0\end{matrix}}\\\left\{\begin{matrix}x\neq5 \\4>x\\4+x>0\end{matrix}}\\-40\\16-x^2>0\end{matrix}}\\\left\{\begin{matrix}x\neq5 \\4>x\\4+x>0\end{matrix}}\\-4
![\left\{{{\frac{2x^2-10x+6}{x-5}-x\leq0}\atop{log_66+log_6(4-x)\leq log_6(16-x^2)}}\right.\\\left\{{{\frac{2x^2-10x+6-x^2+5x}{x-5}\leq0}\atop{log_6(24-6x)\leq log_6(16-x^2)}}\right.\\\left\{{{\frac{x^2-5x+6}{x-5}\leq0}\atop{24-6x\leq 16-x^2}}\right. \left\{{{\frac{2x^2-10x+6}{x-5}-x\leq0}\atop{log_66+log_6(4-x)\leq log_6(16-x^2)}}\right.\\\left\{{{\frac{2x^2-10x+6-x^2+5x}{x-5}\leq0}\atop{log_6(24-6x)\leq log_6(16-x^2)}}\right.\\\left\{{{\frac{x^2-5x+6}{x-5}\leq0}\atop{24-6x\leq 16-x^2}}\right.](https://tex.z-dn.net/?f=%5Cleft%5C%7B%7B%7B%5Cfrac%7B2x%5E2-10x%2B6%7D%7Bx-5%7D-x%5Cleq0%7D%5Catop%7Blog_66%2Blog_6%284-x%29%5Cleq%20log_6%2816-x%5E2%29%7D%7D%5Cright.%5C%5C%5Cleft%5C%7B%7B%7B%5Cfrac%7B2x%5E2-10x%2B6-x%5E2%2B5x%7D%7Bx-5%7D%5Cleq0%7D%5Catop%7Blog_6%2824-6x%29%5Cleq%20log_6%2816-x%5E2%29%7D%7D%5Cright.%5C%5C%5Cleft%5C%7B%7B%7B%5Cfrac%7Bx%5E2-5x%2B6%7D%7Bx-5%7D%5Cleq0%7D%5Catop%7B24-6x%5Cleq%2016-x%5E2%7D%7D%5Cright.)
![\left\{{{\frac{(x-3)(x-2)}{x-5}\leq0}\atop{x^2-6x+8\leq 0}}\right.\\\left\{{{\frac{(x-3)(x-2)}{x-5}\leq0}\atop{(x-2)(x-4)\leq 0}}\right. \left\{{{\frac{(x-3)(x-2)}{x-5}\leq0}\atop{x^2-6x+8\leq 0}}\right.\\\left\{{{\frac{(x-3)(x-2)}{x-5}\leq0}\atop{(x-2)(x-4)\leq 0}}\right.](https://tex.z-dn.net/?f=%5Cleft%5C%7B%7B%7B%5Cfrac%7B%28x-3%29%28x-2%29%7D%7Bx-5%7D%5Cleq0%7D%5Catop%7Bx%5E2-6x%2B8%5Cleq%200%7D%7D%5Cright.%5C%5C%5Cleft%5C%7B%7B%7B%5Cfrac%7B%28x-3%29%28x-2%29%7D%7Bx-5%7D%5Cleq0%7D%5Catop%7B%28x-2%29%28x-4%29%5Cleq%200%7D%7D%5Cright.)
С помощью метода интервалов для первого уравнения находим:
x∈(-∞;2]∪[3; 5)
Для второго:
x∈[2; 4]
Пересечение двух этих множеств:
x∈[3; 4]
С учетом ОДЗ:
x∈[3; 4)